PENGARUH FAMILY CONTROL, UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Anthony Holly; Kunradus Kampo; Robert Jao; Theresia Cindy Lauren Jip (JAF (Journal of Accounting and Finance), 2022)
The purpose of this study is to analyze the effect of family control, size, growth and leverage on firm value. The type of research used in this research is explanatory research. The theory used in this research is agency theory and signaling theory. The sample used is all companies in the consumption sector listed on the IDX with the sampling technique, that is purposive sampling. The sampling criteria are as follows 1.) Companies that have complete financial reports for the 2017-2019 period. 2.) Companies that issue financial statements consecutively during the 2017-2019 period. The research method uses regression linear analysis to determine the relationship between the dependent, and independent variable.The results of this study indicate that family control has a negative and significant effect on firm value. Variable size has a positive and significant effect on firm value. Variable growth has a positive and significant effect on firm value, and leverage has a negative and significant effect on firm value